PELATIHAN SISTEM JURNAL BERPASANGAN BAGI SISWA SMA HARAPAN JAYA - Yanti; Anggraini, Bella; Suroso, Audrey Felicia (Jurnal Serina Abdimas, 2024)
Based on the results of the interview with teachers, there is a problem where currently Harapan Jaya High School class 12 students majoring in science only get a little accounting material at school. Therefore, the solution offered by the PKM Team is to conduct training on the topic "Double Entry System in Accounting For SMA Harapan Jaya Students". The double entry system is basic knowledge in learning accounting, but unfortunately it is quite confusing for beginners so that in many cases it often discourages learning accounting. Training will be held on Friday, August, 23 2024, 10:00 – 12.00 WIB onsite. The training participants were class XII students with a total of 25 students. This PKM activity is carried out using three methods, namely: (1) Presentation of theory given in the form of a module, (2) Using an approach based on Question Practice and Group Discussion, and (3) Using a Games approach in groups as a form of feedback. There are two results from this PKM. First, the PKM training carried out was quite successful in providing an in-depth understanding of the double entry system to the participants. This can be seen from the discussion of the practice questions and games provided, participants who previously did not understand the double entry system, now understand and comprehend the double entry system in accounting. Based on the answers to the questionnaire distributed, participants expressed satisfaction with both the training provided and the instructor's method of conducting the training. ABSTRAK Berdasarkan wawancara dengan Mitra, terdapat permasalahan dimana selama ini siswa SMA Harapan Jaya hanya mendapatkan sedikit materi akuntansi di sekolah. Oleh sebab itu, solusi yang ditawarkan oleh Tim PKM adalah melakukan pelatihan dengan topik “Sistem Jurnal Berpasangan kepada siswa SMA Harapan Jaya”. Sistem Jurnal Berpasangan merupakan ilmu dasar dalam belajar ilmu akuntansi, tetapi sayangnya cukup membingungkan bagi pemula sehingga dalam banyak kasus seringkali melemahkan semangat dalam belajar akuntansi. Pelatihan dilaksanakan pada hari Jumat, tanggal 23 Agustus 2024, pukul 10:00 – 12.00 WIB secara onsite. Peserta pelatihan adalah siswa kelas XII jurusan MIPA dengan jumlah 25 siswa. Kegiatan PKM in dilaksanakan dengan tiga metode yaitu: (1) Pemaparan teori yang diberikan dalam bentuk Modul, (2) Menggunakan pendekatan berbasis Latihan Soal dan Diskusi Berkelompok, dan (3) Menggunakan pendekatan Games secara berkelompok sebagai bentuk umpan balik. Hasil dari PKM ini ada dua. Pertama, pelatihan PKM yang dilaksanakan cukup berhasil dalam memberikan pemahaman yang mendalam tentang Sistem Jurnal Berpasangan kepada peserta pelatihan. Hal ini terlihat dari pembahasan soal-soal latihan dan games yang diberikan, peserta pelatihan yang sebelumnya tidak memahami tentang Sistem Jurnal Berpasangan, sekarang menjadi mengerti dan memahami Sistem Jurnal Berpasangan dalam akuntansi. Berdasarkan jawaban atas kuesioner yang disebarkan, peserta menyatakan puas baik terhadap pelatihan yang diberikan maupun terhadap cara instruktur dalam menyelenggarakan pelatihan.